2019
DOI: 10.3390/electronics8070765
|View full text |Cite
|
Sign up to set email alerts
|

A New Low-Voltage Low-Power Dual-Mode VCII-Based SIMO Universal Filter

Abstract: In this paper, a new low-voltage low-power dual-mode universal filter is presented. The proposed circuit is implemented using inverting current buffer (I-CB) and second-generation voltage conveyors (VCIIs) as active building blocks and five resistors and three capacitors as passive elements. The circuit is in single-input multiple-output (SIMO) structure and can produce second-order high-pass (HP), band-pass (BP), low-pass (LP), all-pass (AP), and band-stop (BS) transfer functions. The outputs are available as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Input and output power gain is the relationship of output power = input power + gain. To evaluate the linear range of the VM biquad filter, consider the BPF, LPF and BRF in Equations (1) to (3). Figure 16 shows the measured P1dB of the BPF at an input power with a center frequency of 102 kHz.…”
Section: Proposed Cfoa-based Vm Multifunction Biquad Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…Input and output power gain is the relationship of output power = input power + gain. To evaluate the linear range of the VM biquad filter, consider the BPF, LPF and BRF in Equations (1) to (3). Figure 16 shows the measured P1dB of the BPF at an input power with a center frequency of 102 kHz.…”
Section: Proposed Cfoa-based Vm Multifunction Biquad Filtermentioning
confidence: 99%
“…Voltage-mode (VM) analog active filters and oscillators using different active components have received extensive attention. Some innovative approaches to realize VM biquad filters [ 1 , 2 , 3 , 4 ] and oscillators [ 5 , 6 , 7 , 8 , 9 ] can be found in the open study. Single-input three-output VM multifunction biquad filters, such as band-pass filter (BPF), low-pass filter (LPF), high-pass filter (HPF) or band-reject filter (BRF), are applied to the phase-locked loop, the high fidelity 3-way speaker, the touch-tone telephone tone decoder, and the phase sensitive detection (PSD) [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The versatile biquad filter that gives multiple filtering functions within the same configuration is well-known as the universal or multifunction filter. In the open literature, this type of active filter has been proposed continuously [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several SIMO second order voltage mode universal filters using different analog active function blocks have been published in the literature . However, these reposed filters have some inconveniences as it has been observed that the active building blocks are not implemented from the commercially available IC [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][36][37][38][39][40][41][42][43]; all capacitors are not grounded [14,18,29,42], the natural frequency is not electronically tuned 36], absence of orthogonal tune of the 0 and Q [13-16, 18-24, 29, 30, 35, 36, 40, 41, 43, 46, 47], the passband voltage gain is not constant during tuning the natural frequency and quality factor [14, 17, 18, 20, 25, 26, 28, 29, 32-34, 36, 38, 39, 42].…”
Section: Introductionmentioning
confidence: 99%